Analisis Pilihan Karir Dan Orientasi Karir Generasi Milenial Dalam Kepuasan Kerja - Irwan Sukmawan; Irma Nurmala Dewi; Hafidz Hanafiah (STIKes Ibnu Sina Ajibarang, 2023)
In general, a person's career is divided into four groups, namely being civil and government civil servants, BUMN employees in various sectors, private employees in various sectors, as well as being an entrepreneur and the like. This research will focus on career choices and orientation in the millennial generation. The millennial generation or generation Z who were born after 1995. Generations that are different from previous generations are the baby boomers, generation X, and generation Y. This research gap has caused policy makers in corporate organizational management to start adapting and seeing what trends are different from other generations. other. This study uses qualitative studies from various recent journals. The results of the study show that most of the millennial generation have career habits with various career patterns, starting from a career as a stepping stone to getting out of their comfort zone by starting a business. The millennial generation is more concerned with salary or income as satisfaction at work.